Why Switch? - Motivations for Self-Substitution of Illegal Drugs. (15th February 2021) - Shapira, Barak; Berkovitz, Ronny; Rosca, Paola; Lev-Ran, Shaul; Kaptsan, Alexander; Neumark, Yehuda
Abstract: Background: Self-substitution is the conscious switch from one drug to another for reasons such as price, availability, desired effect, or perceived benefit of the substitute drug. Purpose/Objectives: This study aimed to describe drug use patterns and motivations associated with substitution. We examined correlates of lifetime substitution among individuals with substance use disorder. Methods: A cross-sectional study of 771 treatment-enrolled individuals. We used self-report for determining the lifetime prevalence, correlates, and motivations for substitution. Results: Of the 771 respondents, 570 (73.9%) reported ever substituting their preferred substance. The main incentives for substitution were availability (23.7%) and curiosity (20.2%). Among heroin or cannabis preferers, improved effects or less adverse effects of the substitute drug, self-medication, and managing withdrawal symptoms were significant substitution incentives. Increased odds for substitution were observed for past 12 months use of cannabis (OR = 1.51, CI = 1.06-4.52), prescription opioids (OR = 2.86, CI = 1.81-4.52), novel psychoactive substances (OR = 2.68, CI = 1.64-4.36), and repeated admission (OR = 1.50, CI = 1.05-2.14). Older age at onset-of-use was negatively associated with substitution (OR = 0.95, CI = 0.93-0.98). Conclusions: Self-substitution of one substance for another is a highly prevalent behavior among treatment-enrolled patients with substance use disorder. Clinicians caring for substance use disorder patients should be aware of substitution patterns involving the use of highly potent substances, which constitutes a risk to patients. Results underscore the benefit of substitution patterns analyses, as they reveal important information on the characteristics of persons who use drugs and their motivations.